2010
DOI: 10.1111/j.1747-0285.2010.01027.x
|View full text |Cite
|
Sign up to set email alerts
|

Computational Studies on Effects of MDMA as an Anticancer Drug on DNA

Abstract: This research is designed to further understand the effects of the novel drug MDMA on biologic receptor of DNA. The ultimate goal is to design drugs that have higher affinity with DNA. Understanding the physicochemical properties of the drug as well as the mechanism by which it interacts with DNA should ultimately enable the rational design of novel anticancer or antiviral drugs. Molecular modeling on the complex formed between MDMA and DNA presented this complex to be fully capable of participating in the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 41 publications
(61 reference statements)
0
27
0
1
Order By: Relevance
“…[1][2][3][4][5] Recently many theoretical approaches for prediction redox potentials for wide range of compounds have been developed. [3][4][5][6][7][8] Most of them evaluate Gibbs free energy of reduction in solution in two steps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Recently many theoretical approaches for prediction redox potentials for wide range of compounds have been developed. [3][4][5][6][7][8] Most of them evaluate Gibbs free energy of reduction in solution in two steps.…”
Section: Introductionmentioning
confidence: 99%
“…4 It has also been found that a popular B3LYP functional showed large deviations from the experimental values for both nitrocompounds 6 and quinones. 5 The CBS-4MB method in conjunction with SM5.42R model for calculation of solvent effects provides a mean unsigned error of about 0.19 V for polypyridinic derivatives, nitrobenzene and benzophenone in dimethylformamide (DMF). 7 The purpose of this study is to find a computational protocol which will be based on computationally inexpensive DFT approximations, will accurately predict reduction potential for such groups of environmental pollutants as nitroaromatic compounds, quinones and azacyclic compounds (models of high nitrogen containing explosives).…”
Section: Introductionmentioning
confidence: 99%
“…The value is well within the range of pK a s reported for several other compounds structurally related to DND. [21][22][23] At pH 9.0-12.9, oxidation of DND occurred by the abstraction of electron only. Hence EC (electron transfer reaction followed by chemical reaction )/CE (chemical reaction followed by electron transfer reaction ) mechanism switched to EE (electron transfer reaction followed by electron transfer reaction) mechanism after pK a .…”
Section: Resultsmentioning
confidence: 99%
“…The reason for the selection of DFT/3-21G was its success in charge calculations as testified by other investigators. 21,22 Charge distributions on keto and enol forms of IQN have been depicted in Figs. 11 and 12.…”
Section: H598mentioning
confidence: 99%